Okvirna analiza debelinske strukture izbranega drevja za posek v gozdovih Slovenije v obdobju 1995-2008 - Veselič, Živan (Gozdarski vestnik, 2009)
Basing on the example of 28 forest management units (FMU) comprising more than 90% state owned forests and of 60 FMU comprising more than 90% private forests, the article presents the analysis of the diameter structure of the trees selected for cutting in the state and private forests in the period 1995-2008. We analyzed the FMUs where the wood stocks were identified exclusively or almost exclusively on the constant sample planes; therefore, the analyzed forests were to some extent above the average with regard to the production capabilities of the habitats and stand conditions. The diameter structure of the trees selected for cutting is compared to the diameter structure of the trees in the forest stands and with the diameter structure of the trees in the model forest. The data on the forest stands are based on the stand measurements on the constant sample planes and the data on the modelforest on the Halaj tables (spruce: SI100 = 30, mountain spruce, production level 2, SP 10.2 and beech: SI100 = 28, production level 2, SP 8.2). The actual ratio of coniferous and deciduous trees wood stock, which is completely equal in the analyzed forests regardless of their ownership: 48.5 %: 51.5 %, was taken into account.
Keywords: gozdovi; državni gozdovi; zasebni gozdovi; posek; lesne zaloge; Slovenia; Slovenija